UNCERTAINTY IN CATERING WORKERS’ WAGE PAYMENT PRACTICES IN MEDAN JOHOR FROM THE PERSPECTIVE OF DSN-MUI FATWA NO. 112/DSN-MUI/IX/2017 ON THE IJARAH CONTRACT - Yulia Syafitri Harahap; Muhibbussabry Muhibbussabry (Journal Analytica Islamica, 2026)
Wage payment practices are a crucial element in employment relationships because they relate to legal certainty and the protection of workers' economic rights. However, in the informal sector—particularly home-based catering businesses—wage mechanisms are often implemented without a clear agreement regarding the amount and timing of payments. This study aims to analyze wage payment practices in catering businesses in Medan Johor District from the perspective of Government Regulation Number 36 of 2021 concerning Wages and DSN-MUI Fatwa Number 112/DSN-MUI/IX/2017 concerning Ijarah Contracts. This study uses a qualitative approach with juridical-empirical methods through in-depth interviews with workers and catering business owners and an analysis of relevant regulations and fatwas. The results show that wage payments are fluctuating and uncertain, depending on the number of orders, without a clear agreement from the start of the employment relationship. This practice does not comply with the principle of wage certainty in labor law and contradicts the principle of clarity of ujrah in ijarah contracts. This research contributes to strengthening the study of labor law and Islamic law by emphasizing the urgency of wage clarity as an instrument of justice and protection for workers in the informal business sector.